Molecular and morphological evaluation of the aphid genus Hyalopterus Koch (Insecta: Hemiptera: Aphididae), with a description of a new species - Lozier, Jeffrey D.; Foottit, Robert G.; Miller, Gary L.; Mills, Nicholas J.; Roderick, George K. (Zootaxa, 2008)
Aphids in the genus Hyalopterus Koch (Hemiptera: Aphididae) are pests of stone fruit trees in the genus Prunus globally, causing damage directly through feeding as well as transmission of plant viruses. Despite their status as cosmopolitan pests, the genus is poorly understood, with current taxonomy recognizing two, likely paraphyletic, species: Hyalopterus pruni (Koch) and Hyalopterus amygdali (Blanchard). Here we present a systematic study of Hyalopterus using a molecular phylogeny derived from mitochondrial, endosymbiont, and nuclear DNA sequences (1,320 bp) and analysis of 16 morphometric characters. The data provides strong evidence for three species within Hyalopterus, which confirms previous analyses of host plant usage patterns and suggests the need for revision of this genus. We describe a new species H. persikonus Miller, Lozier & Foottit n. sp., and present diagnostic identification keys for the genus.